Reviews - Edward J. Sullivan; Gabriele Rico; Megan Brown; Kim McCollum-Clark (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
Reviews Edward J. Sullivan. Ken Wilber: Thought as Passion. (Frank Visser, 2003). Gabriele Rico. A Way to Move: Rhetorics of Emotion and Composition Studies. (Ed. Dale Jacobs and Laura R. Micciche, 2003). Megan Brown. Living the Narrative Life: Stories as a Tool for Meaning Making. (Gian S. Pagnucci, 2004). Kim McCollum-Clark. Personally Speaking: Experience as Evidence in Academic Discourse. (Candace Spigelman, 2004).